2017
DOI: 10.21522/tijbms.2016.02.01.art005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Epigenetic and DNA Damage Repairing Molecular Mechanisms of L-Carnitine and its Congeners against Aging and Age-Related Neurodegenerative Diseases

Abstract: Aging is an ubiquitous biological phenomena characterized by ever-increasing susceptibility to diseases due to increased oxidative stress (OS) and an ultimate severe non-repairable membrane molecular and mitochondrial damages coupled with energy (ATP) depletion. L-Carnitine (β-hydroxy-γ-trimethyl amino butyrate) and its congeners plays an essential role in mitochondrial ATP synthesis while being a powerful anti-inflammatory antioxidant and an organic, non-ionic bi-phasic osmolytes. L-carnitine exerts antimutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…L-Carnitine (l-car) is required for β-oxidation of longchain fatty acids in mitochondria [19]. It also showed antioxidant properties, such as boosting the antioxidant system [20], preventing lipid peroxidation [21], protecting DNA and cell membranes from damage caused by ROS [22,23], helping to normalize age-related changes [24,25], and also increasing the immune system's ability [26]. Furthermore, some recent studies have reported the anti-infammatory [27] and neuroprotective [28,29] efects of l-car and its positive efects on some diseases [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…L-Carnitine (l-car) is required for β-oxidation of longchain fatty acids in mitochondria [19]. It also showed antioxidant properties, such as boosting the antioxidant system [20], preventing lipid peroxidation [21], protecting DNA and cell membranes from damage caused by ROS [22,23], helping to normalize age-related changes [24,25], and also increasing the immune system's ability [26]. Furthermore, some recent studies have reported the anti-infammatory [27] and neuroprotective [28,29] efects of l-car and its positive efects on some diseases [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Aging is a ubiquitous biological phenomena, characterized by ever-increasing susceptibility to diseasesmitochondrial damages, and ultimately death. (8) Aging is an ubiquitous biological phenomena characterized by ever-increasing susceptibility to diseases due to increased oxidative stress (OS). (9) Current evidence suggests both resveratrol and pterostilbene may be modulators for agedrelated neurodegeneration, obese, diabetes, and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%